2020
DOI: 10.1002/nbm.4362
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate‐lactate exchange and glucose uptake in human prostate cancer cell models. A study in xenografts and suspensions by hyperpolarized [1‐13C]pyruvate MRS and [18F]FDG‐PET

Abstract: Reprogramming of energy metabolism in the development of prostate cancer can be exploited for a better diagnosis and treatment of the disease. The goal of this study was to determine whether differences in glucose and pyruvate metabolism of human prostate cancer cells with dissimilar aggressivenesses can be detected using hyperpolarized [1‐13C]pyruvate MRS and [18F]FDG‐PET imaging, and to evaluate whether these measures correlate. For this purpose, we compared murine xenografts of human prostate cancer LNCaP c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
1
2
0
Order By: Relevance
“…Finally, we demonstrated that PC-3 cells converted HP 13 C-pyruvate to lactate at a higher rate than LNCaP cells, consistent with results from Zacharias et al who examined PC-3 xenografts using HP 13 C-pyruvate MRI [39]. However, recent work by van Heijster et al [40] did not reveal a significant difference using the same cell lines, which could be attributed to the much higher concentration of hyperpolarized pyruvate used in our study. Further, we have shown in an inducible model of castration resistance that ADPC tumors are much less glycolytic than CRPC tumors and can be monitored noninvasively using HP [1- 13 C]pyruvate based on a significant increase in the HP 13 C -lactate/ 13 C -pyruvate ratio.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, we demonstrated that PC-3 cells converted HP 13 C-pyruvate to lactate at a higher rate than LNCaP cells, consistent with results from Zacharias et al who examined PC-3 xenografts using HP 13 C-pyruvate MRI [39]. However, recent work by van Heijster et al [40] did not reveal a significant difference using the same cell lines, which could be attributed to the much higher concentration of hyperpolarized pyruvate used in our study. Further, we have shown in an inducible model of castration resistance that ADPC tumors are much less glycolytic than CRPC tumors and can be monitored noninvasively using HP [1- 13 C]pyruvate based on a significant increase in the HP 13 C -lactate/ 13 C -pyruvate ratio.…”
Section: Discussionsupporting
confidence: 91%
“…These characteristics are important considerations for future studies and increasingly support identifying tumor types in which harnessing radiosensitizing properties through lactate metabolism inhibition has the greatest therapeutic benefit. For example, additional imaging techniques, such as 13 C magnetic resonance spectroscopy, can better provide dynamic imaging of lactate metabolic reprogramming (115)(116)(117). A recent clinical trial explored deescalation of radiation to 30 Gy for patients with human papillomavirus-associated oropharyngeal tumors who had no hypoxia at baseline using dynamic fluorine-18-labeled fluoromisonidazole PET or resolution of hypoxia during intratreatment PET; while patients with persistent hypoxia received 70 Gy (118).…”
Section: Future Directionsmentioning
confidence: 99%
“…Dissolution DNP has been used to investigate metabolic pathways and to study enzymatic activities. Small hyperpolarized 13 C-labeled substrates, such as 1- 13 C-pyruvic acid or 1- 13 C-fumarate, have been successfully used to detect aberrant metabolism in cell suspensions, animal models, and human tumors. However, the hyperpolarized state is relatively short-lived, and the polarization will restore to thermal equilibrium with the relaxation time constant T 1 . The majority of hyperpolarized 13 C-labeled molecules have a T 1 in the order of 1 min or less .…”
Section: Introductionmentioning
confidence: 99%